Psychological and pcychoemotional disorders of family functioning - Prib, Hlib; Bondar, Svitlana (Psychological Prospects Journal, 2019)
The article focuses on the issues of psychological and pcychoemotional disorders of family functioning. The article proposes analysis results of trait combinations of men and women, who are infidelity survivors, as well as defines possible ways of the "family conflict" development. Men and women with a demonstrative accentuation type are prone to artistry, showing off, emotional lability, conflicts with egocentric traits, sometimes inadequate assessment of their actions. The basis of such behavior is the desire to attract maximum attention for the purpose of influence (in particular, control the behavior of the opposite sex) or the desire in some situations to feel weaker to attract attention, often with aggressive signs in the absence of the partner`s desired response. Persons with excitable accentuation type manifest weakness of emotional control, poor impulse control, proneness to conflicts, poor personal duties management. Persons with hyperthymic accentuation type have "poor sense of distance", heightened irritability, temper tantrums. Men and women with emotive accentuation type manifest weaker ability to express feelings, mood, fears related to public’s attitude to them. Based on the research results two types of personality traits accentuation having a detrimental effect on family functioning have been identified for men and women: the first – a combination of dysthymic accentuation type. and sticked accentuation. A leading feature in the formation of family relations is a predisposition to stuck affect. The type with satisfaction with marriage being characterised as "absolutely adverse" and "adverse". The second – a combination of anxiety accentuation type and emotive accentuation type. A leading feature in men and women was a tendency to mood disorders. Often anxiety was associated with the humiliation of their human dignity as a result of adultery partner. The marriage satisfaction being characterised as "adverse" and "more adverse". Future research of the subject should focus on scientific evidence and development of specific family counseling for family dysfunction caused by infidelity.